OP0207 URATE-LOWERING THERAPY WITH VERINURAD AND FEBUXOSTAT REDUCES SERUM URIC ACID AND ALBUMINURIA IN HYPERURICEMIC PATIENTS WITH DIABETES. (June 2019) - Terkeltaub, Robert; Dronamraju, Nalina; Johansson, Susanne A; Parkinson, Joanna; Johnsson, Eva; Erlandsson, Fredrik; Stack, Austin
Abstract : Background: Hyperuricemia is implicated as a major risk factor for chronic kidney disease (CKD), and emerging clinical data suggest that lowering serum uric acid (sUA) may protect kidney function by reducing albuminuria and slowing the rate of CKD progression. We evaluated the efficacy and safety of an intensive sUA-lowering strategy of verinurad (RDEA3170), a novel urate transport inhibitor of URAT1, and febuxostat in patients with Type 2 diabetes mellitus (T2DM) and albuminuria (clinicaltrials.gov: NCT03118739 ). Objectives: To compare the efficacy of verinurad + febuxostat to placebo in reducing albuminuria in patients with T2DM. Methods: A Phase 2 parallel group, randomised, double-blind, placebo-controlled clinical trial. Patients were assigned 1:1 to either verinurad 9 mg + febuxostat 80 mg (n=32) or placebo (n=28). Inclusion criteria: aged ≥18 years, sUA concentration ≥6.0 mg/dL, estimated glomerular filtration rate (eGFR) ≥30 mL/min/1.73 m 2, urinary albumin-to-creatinine ratio (UACR) 30–3500 mg/g and T2DM diagnosis. Exclusion criteria: history of gout or recent treatment with urate-lowering therapy. The primary endpoint was change in UACR. Secondary endpoints included sUA, renal function biomarkers, and eGFR. Results: Baseline characteristics were similar between groups. For treatment vs placebo, respectively, mean (SD) sUA was 7.5 (1.6) vs 7.0 (0.8) mg/dL, eGFR was 59.2 (25.3) vs 68.1 (23.2) mL/min/1.73 m 2, and UACR was 459 (825) vs 412 (548) mg/g at baseline. The study met the primary endpoint as verinurad/febuxostat reduced UACR by 39% vs placebo after 12 weeks of treatment ( p =0.07, predetermined α=0.1). Least squares (LS) mean% change in eGFR at 24 weeks from baseline was –1.73% for verinurad/febuxostat vs +0.55% for placebo ( p =0.71). LS mean% change in sUA was –57% in the verinurad/febuxostat vs an increase of 7% in the placebo group at 12 weeks ( p <0.0001). This effect was sustained at 24 weeks (62% reduction with verinurad/febuxostat vs 5% increase with placebo; p <0.0001). Excluding patients with prior gout avoided the need to administer gout prophylaxis, and only one gout flare-up (3%) was reported in the verinurad/febuxostat group. Most adverse events (AEs) observed were mild to moderate. AEs reported in more than one patient on active treatment were diarrhoea, dizziness, and nasopharyngitis. Conclusion: Treatment with verinurad + febuxostat significantly reduced hyperuricemia and albuminuria in patients with T2DM. The effect was rapid, and the improvement was sustained through Week 24, suggesting that an intensive urate-lowering strategy that combines a URAT1 inhibitor with a xanthine oxidoreductase inhibitor may protect against the progression of diabetic kidney disease. Further studies are planned to confirm the efficacy of a verinurad-led urate-lowering strategy in preventing CKD progression. Disclosure of Interests: Robert Terkeltaub Consultant for: AstraZeneca, Horizon, SOBI, and Selecta, Nalina Dronamraju Employee of: AstraZeneca, Susanne A Johansson Employee of: AstraZeneca, Joanna Parkinson Shareholder of: AstraZeneca, Employee of: AstraZeneca, Eva Johnsson Employee of: AstraZeneca, Fredrik Erlandsson Employee of: AstraZeneca, Austin Stack Consultant for: AstraZeneca, Grunenthal, and Menarini